Early-age Hydration Characteristics of Composite Binder Containing Graphite Powder - He, Wei; Song, Shaomin; Meng, Xia; Zhang, Pengchong; Sun, Xu (Journal of Wuhan University of Technology. Materials science edition, 2022)
The early-age hydration characteristics of composite binder containing graphite powder (GP) with two different finenesses were investigated by determining the hydration heat, thermo gravimetric, morphology of hardened paste as well as the compressive strength of mortar. The experimental results show that: replacing 2%–6% of cement with graphite powder significantly improves the piezoresistive effect of early age mortar, can be used to monitor accidental loads caused by dropped objects, collisions, or other accident events, and thus avoids initial damage. Some GP provides additional nucleation sites that lead to a fast formation of hydration products (nucleation-site effect). However, due to the almost hydrophobic water contact angle, most of the GP causes a large number of micro-cracks in the hydrated paste (gap effect). Because of the lamellar shape and high surface energy, GP is easily balled and can not be uniformly distributed in the composite, resulting in clumping together and wrapping some of the cement particles (barrier effect). Due to nucleation-site effect, when the dosages of coarse and fine GP reached 2% and 4%, 1 d strength were increased by 9.1% and 9.6%, respectively. At 3 days, as the interior damage caused by the gap effect gradually increased, and the retarding effect on cement hydration caused by barrier effect was enhanced. GP has an obvious negative effect on compressive strength. However, micro-cracks caused by fine GP are less, so its negative effect on 3 d compressive strength is lower.